From innovation to implementation : wearable data driven analytics and private health insurance in the United States - Soliño Fernández, Diego; Štěrbová, Ludmila, 1957-; Feigl Ding, Eric; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2017)
The intent of this research was to define which wearable data-driven services addvalue to two key stakeholders in the healthcare system in the U.S.; consumers(insured or potential applicants) and private health insurers. In other words, theoverall goal of this master thesis was to discover new wearable data-driven analyticsor services that create a win-win scenario for consumers and private health insurersin the U.S., and, thus, could be implemented in the future.
Vedoucí práce: Ludmila Štěrbová
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2017
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2017
Způsob přístupu: Internet
Keywords: international business - central european business realities [obor dipl. práce]; diplomové práce; master's theses